SOME ASPECTS OF CONDUCTING GMP INSPECTIONS IN RUSSIA - G. N. Gildeeva; V. I. Yurkov (Сеченовский вестник, 2018)
Development of pharmaceutical industry in Russia requires for a common approach to the qualification and standardization of manufacturing process for drug products. To achieve this goal the package of relevant legal Acts was approved in Russia in 2015-2016, aimed at harmonizing the rules of Good Manufacturing Practices - GMP, in particular in the field of inspection.